Interaction of Participant Characteristics and Type of AAC With Individuals With ASD: A Meta-Analysis - Ganz, Jennifer B.; Mason, Rose A.; Goodwyn, Fara D.; Boles, Margot B.; Heath, Amy K.; Davis, John L. (American journal on intellectual and developmental disabilities, 2014)
Individuals with autism spectrum disorders (ASD) and complex communication needs often rely on augmentative and alternative communication (AAC) as a means of functional communication. This meta-analysis investigated how individual characteristics moderate effectiveness of three types of aided AAC: the Picture Exchange Communication System (PECS), speech-generating devices (SGDs), and other picture-based AAC. Effectiveness was measured via the Improvement Rate Difference. Results indicated that AAC has small to moderate effects on speech outcomes, and that SGDs appear to be most effective when considering any outcome measure with individuals with ASD without comorbid intellectual/developmental disorders (IDD). PECS appears to be most effective when considering any outcome measure with individuals with ASD and IDD. SGDs and PECS were the most effective type of AAC for preschoolers, when aggregating across outcome measures. No difference was found between systems for elementary-aged and older individuals.